Evolution of microbial community and chemical properties of a sourdough during the production of Colomba, an Italian sweet leavened baked product. (December 2017) - Raimondi, Stefano; Amaretti, Alberto; Rossi, Maddalena; Fall, Papa Abdoulaye; Tabanelli, Giulia; Gardini, Fausto; Montanari, Chiara
Abstract: A sourdough for the industrial production of Colomba, a traditional Italian sweet-leavened baked good, was characterized in terms of microbiota composition, pH, aw, carbohydrates, organic acids, and VOCs. pH of the ripened sourdough was low (3.55), and the content of acetic acid limited (0.77 g/kg). A small biodiversity, in terms of both LAB and yeasts, was observed. Culture dependent analyses identified two biotypes of Lactobacillus sanfranciscensis and a dominant yeast species, Torulaspora delbrueckii. Metataxonomic analysis confirmed bacterial composition, whereas Candida humilis was the most represented yeast. The VOCs profile was strongly affected by bakers' yeast addition, resulting in higher amounts of acetaldehyde, acetoin, ethanol, and phenethyl alcohol. As a whole, a stable and abundant microbial community loosing competitiveness only after addition of S. cerevisiae was described. This robustness and simplicity can represent an advantage in terms of stable and easier propagation, allowing the production of more reproducible lots of Colomba . Highlights: The microbiota of a Colomba sourdough propagated at 13 °C was studied. The evolution of aroma profile during processing was affected by bakers' yeast addition. This sourdough was characterized by a low biodiversity in terms of both LAB and yeasts. LAB population of sourdough was dominated by two biotypes of L. sanfranciscensis . Metataxonomic and culture dependent approaches differed for yeast identification.